Keterampilan Pandai Besi Pembuatan Badik yang Digunakan pada Tradisi Angngaru Lokal Di Kampung Beru Parigi, Kabupaten Gowa - Ds, Agung Fadhil; Putri, Sulfiana Mansyur (CV. ITTC INDONESIA, 2025)
This study explores the connection between the ritual of badik (traditional dagger) forging on the 10th of Muharram and the practice of angngaru within the local community of Kampung Beru, Parigi Village, Tinggimoncong Subdistrict, Gowa Regency, South Sulawesi. The forging of badik on this particular date is regarded not merely as a technical craft, but as a sacred ritual believed to possess protective and apotropaic powers, coinciding with the spiritual significance of Ashura, a day associated with blessings and protection. On the other hand, angngaru—originally a traditional oath of loyalty performed by warriors to their king—carries deep symbolic and spiritual meanings embedded within the Bugis-Makassar cultural framework. Using a symbolic anthropology approach and ethnographic methods, this research reveals that the badik functions not only as a physical weapon but also as a cultural and spiritual medium integrated into the angngaru tradition. The ritual forging of badik during sacred times such as the 10th of Muharram enhances the spiritual dimension of angngaru, serving as an expression of bravery, ancestral reverence, and cultural identity. Thus, a strong correlation exists between the ritualized production of badik and the practice of angngaru, both of which represent interconnected cultural systems that preserve the cosmology, local values, and spirituality of the people of Kampung Beru, Gowa.